2020
DOI: 10.1016/j.fertnstert.2020.08.170
|View full text |Cite
|
Sign up to set email alerts
|

Slowflowhd Application in Fet Cycles

Abstract: OBJECTIVE: To assess the incidence and ultrasonographic characteristics of cesarean scar niches after uterine closure by double-layer barbed suture.DESIGN: This was a prospective case-control study. MATERIALS AND METHODS: Women who underwent elective cesarean section at R 38 weeks of gestation were enrolled. Exclusion criteria were a previous cesarean section or uterine surgery. Low transverse hysterotomy was closed either by a double-layer unidirectional barbed suture or by a conventional double-layer smooth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…But there are also dissenters. Sadek et al (2022) found pregnancy and live births were associated with a lower mean percentage drop in blood flow from day 15 to the day of transfer and elevated RI and S/D ratio on transfer day. Sardana said (Sardana et al, 2014) that the presence of endometrial blood flow was highly correlated with the cycle outcome in HRT-FET cycles, and the embryo implantation rate and clinical pregnancy rate of the endometrial blood flow signal group were significantly higher than those with the absented blood flow group in the subendometrial-endometrial region.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…But there are also dissenters. Sadek et al (2022) found pregnancy and live births were associated with a lower mean percentage drop in blood flow from day 15 to the day of transfer and elevated RI and S/D ratio on transfer day. Sardana said (Sardana et al, 2014) that the presence of endometrial blood flow was highly correlated with the cycle outcome in HRT-FET cycles, and the embryo implantation rate and clinical pregnancy rate of the endometrial blood flow signal group were significantly higher than those with the absented blood flow group in the subendometrial-endometrial region.…”
Section: Discussionmentioning
confidence: 84%
“…Ultrasound-measured endometrial blood flow is one of the important evaluation indicators of endometrial morphology. There have been many studies about it (Son et al, 2014;Koo et al, 2018;Sadek et al, 2022), but ultrasound indicators which predicted of the outcomes of ART existed for endometrial blood flow are controversial. The relationship between endometrial blood flow and pregnancy outcome is even more uncertain.…”
Section: Introductionmentioning
confidence: 99%